2017
DOI: 10.1021/acsami.7b02696
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antibacterial Effects of Covalently Attached Biomembrane-Mimic Polymer Grafts on Gore-Tex Implants

Abstract: Expanded polytetrafluoroethylene (ePTFE), also known as Gore-Tex, is widely used as an implantable biomaterial in biomedical applications because of its favorable mechanical properties and biochemical inertness. However, infection and inflammation are two major complications with ePTFE implantations, because pathogenic bacteria can inhabit the microsized pores, without clearance by host immune cells, and the limited biocompatibility can induce foreign body reactions. To minimize these complications, we covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…Moreover, it must be noted, that the cytoarchitectonics of the peri-implant mucosa differs significantly from the gingiva of the natural teeth. It is characterized by scar nature (low percentage of fibroblasts, irregulars collagen fibers structure), and a lack of periodontal space (diminished blood and interstitial blood flow), which decreases its permeability (Zhang et al., 2012 ; Jin et al., 2017 ).…”
Section: Antibacterial Biomaterials Active Surface Finishingmentioning
confidence: 99%
“…Moreover, it must be noted, that the cytoarchitectonics of the peri-implant mucosa differs significantly from the gingiva of the natural teeth. It is characterized by scar nature (low percentage of fibroblasts, irregulars collagen fibers structure), and a lack of periodontal space (diminished blood and interstitial blood flow), which decreases its permeability (Zhang et al., 2012 ; Jin et al., 2017 ).…”
Section: Antibacterial Biomaterials Active Surface Finishingmentioning
confidence: 99%
“…7f). It was reported that the serious infiltration of inflammatory cells was mainly caused by bacterial infection rather than by the antimicrobial implants [72][73][74] . Overall, Ti-AMP-P3 and Ti-Dual-P4 rods have the best antimicrobial activity.…”
Section: Mfi Of Rgdmentioning
confidence: 99%
“…Sunah Kang et al developed silicone implants that could reduce the fibrous capsule with a dense coating of 2-methacryloxyethyl phosphorylcholine (MPC) polymer. MPC is a zwitterionic polymer that mimics the head group of phosphatylcholine lipids in the plasma membrane and is widely applied as a coating material on orthopedic, cardiovascular, and ophthalmologic medical devices [ 80 , 81 ]. Heat-induced polymerization was applied for covalently grafted MPC around the silicone implant.…”
Section: Surface Modification Using Polymersmentioning
confidence: 99%